﻿The effect of anticoagulant therapy for idiopathic pulmonary fibrosis in real life practice - ﻿Tomassetti, S.; ﻿Ruy, J.H.; Gurioli, C.; Ravaglia, C.; Buccioli, M.; Tantalocco, P.; Decker, P.A.; Cavazza, A.; Dubini, A.; Agnoletti, V.; Gurioli, C.; Casoni, G.L.; et al. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Background: IPF is a common form of interstitial lung disease for which there is no effective therapy and usually results in death. Two previous contradictory studies showed anticoagulant therapy  to be associated with both improved and worsened survival, respectively. Objective: The objective of this retrospective cohort study was to evaluate the effect of anticoagulant therapy on the survival and disease progression of patients with idiopathic pulmonary fibrosis (IPF) in real clinical practice. Methods: We compared the clinical characteristics, time to disease progression, incidence of acute exacerbation, and survival of 25 (20%) IPF patients receiving anticoagulant therapy to the remaining 97 IPF patients not receiving anticoagulant therapy. In addition we conducted a sensitivity analysis using as comparator a group of 25 patients matched by age, sex, functional impairment, cardiac comorbidities and pulmonary hypertension. Results: Patients on anticoagulant therapy had a worse 1- and 3-year survival (84% and 53% versus 89% and 64% in the non-anticoagulant group, respectively), a difference that persisted after adjusting for age and comorbidities (hazard ratio 3.1 - 95% confidence interval, 1.4 to 7.0; p=0.006) and after comparison with the matched group (adjusted HR=4.8, 95% CI: 1.8-12.8; p=0.002). IPF patients on anticoagulant therapy had a shorter interval to disease progression ( 0.7 years versus 1.6 years, adjusted HR 2.2 -95% CI, 0.96 to 5.1; p=0.063) confirmed also in the analysis with matched subgroups (HR=2.7 (95% CI: 1.2-6.5); p=0.023). The incidence of acute exacerbations did not differ in the two groups (22% versus 23%). Two patients (8%) experienced anticoagulant treatment related complications and included an episode of hemorrhagic shock. Conclusion: In this retrospective study patients treated with anticoagulants had a worse survival and a shorter interval to disease progression. This support the recent finding that warfarin worsen the respiratory status and survival of IPF patients.